2005
DOI: 10.1111/j.1523-1755.2005.67137.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypertension on the risk for kidney cancer in Korean men

Abstract: This study supports the hypothesis that hypertension is an independent risk factor of kidney cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…In men, there was no association with blood pressure. The association of blood pressure with risk of renal cell cancer has been investigated in a number of cohort (Fraser et al, 1990;Grove et al, 1991;Coughlin et al, 1997;Heath et al, 1997;Chow et al, 2000;Choi et al, 2005;Flaherty et al, 2005;Fryzek et al, 2005;Lindgren et al, 2005;Schouten et al, 2005) and case -control (McLaughlin et al, 1995;Yuan et al, 1998;Shapiro et al, 1999) studies, using as principal exposure variable either recorded blood pressure or reported hypertension. In men, recorded blood pressure has shown a convincing exposure -response gradient related to renal cell cancer risk (Coughlin et al, 1997;Chow et al, 2000).…”
mentioning
confidence: 99%
“…In men, there was no association with blood pressure. The association of blood pressure with risk of renal cell cancer has been investigated in a number of cohort (Fraser et al, 1990;Grove et al, 1991;Coughlin et al, 1997;Heath et al, 1997;Chow et al, 2000;Choi et al, 2005;Flaherty et al, 2005;Fryzek et al, 2005;Lindgren et al, 2005;Schouten et al, 2005) and case -control (McLaughlin et al, 1995;Yuan et al, 1998;Shapiro et al, 1999) studies, using as principal exposure variable either recorded blood pressure or reported hypertension. In men, recorded blood pressure has shown a convincing exposure -response gradient related to renal cell cancer risk (Coughlin et al, 1997;Chow et al, 2000).…”
mentioning
confidence: 99%
“…There is evidence that renal carcinoma is associated with diuretic use (Grossman et al, 2001), although this is not generally accepted (Choi et al, 2005;Fryzek et al, 2005). Prenatal exposure to diuretics was associated with an increased risk of childhood brain tumours (Preston-Martin et al, 1982), which could not be confirmed by subsequent studies (Kuijten et al, 1990;McCredie et al, 1994;McKean-Cowdin et al, 2003).…”
Section: Discussionmentioning
confidence: 39%
“…On the other hand, Choi et al [30] reported no association between diabetes mellitus and the risk of kidney cancer in the Korean population.…”
Section: Risk Factors Medical Conditionsmentioning
confidence: 99%
“…Hypertension: Hypertension [1,2,17,31] has been reported to be a risk factor for kidney cancer in Western countries [1,2,17,24,26] as well as in East Asian countries (e.g., Japan [5,8], Taiwan [29], Korea [30]). In the JACC study, there is a positive association between hypertension and the development of kidney cancer (age-and sex-adjusted HR=4.27, 95% CI: 2.07 to 8.79) in the population of Japan [8].…”
Section: Risk Factors Medical Conditionsmentioning
confidence: 99%